Gender Differences in Predrinking Behavior Among Nightclubs' Patrons. (8th June 2015) - Santos, Mariana G. R.; Paes, Angela T.; Sanudo, Adriana; Andreoni, Solange; Sanchez, Zila M.
<x xml:space="preserve">Abstract</x> Background Drinking before entering nightclubs (predrinking) seems to be associated with an increase in alcohol‐related harm. This study aims to investigate gender differences in predrinking behavior and to evaluate its association with risk behaviors practiced inside nightclubs. Methods Individual‐level data were collected by a portal survey of 2, 422 patrons at the entrance and 1, 833 patrons at the exit of 31 nightclubs located at São Paulo, Brazil. The nightclubs were selected by 2‐stage sampling with probability proportional to the establishments' capacity in the first stage and a systematic sample of patrons in the entrance line in the second stage. Breath alcohol concentration (BrAC) was measured at the entrance and exit. Face‐to‐face interviews identified predrinking characteristics and risk behaviors. Weighted analyses were stratified by gender. Results Predrinking was practiced by 49.2% (95% confidence interval [CI] = 42.7 to 55.8) of the male patrons and 29.0% (95% CI = 20.6 to 38.9) of the female patrons (p < 0.001) on the day of the interview. When considering only predrinkers, men and women showed similar BrAC at entrance and exit and similar proportion of alcoholic intoxication (BrAC ≥ 0.38 mg/l). In both genders, people who practiced predrinking on the day of the interview were more likely to drink inside the nightclub, compared to those who did not practice predrinking (p < 0.001). Among men, the practice of predrinking increased the chance of "drinking and driving" after leaving the nightclub (odds ratio [OR] = 6.9, 95% CI = 4.1–11.5, p < 0.001). Among women, the practice of predrinking increased the chances of experiencing sexual harassment in the nightclub (OR = 2.9, 95% CI = 1.3 to 6.6, p = 0.010). Conclusions Predrinking is more prevalent among men; however, men and women who engaged in predrinking have a similar pattern of alcohol consumption and exit BrAC. The fact that risk behaviors and illicit drug use were associated with predrinking but differ between genders suggests that a gender‐specific approach should be used in tailored interventions to prevent alcohol‐related harm in nightclubs.